Dimethyl‐2‐[(acridin‐9‐yl)methylidene]‐malonate as fluorescent probe for histochemical analysis. Issue 6 (22nd January 2017) - Almeida, Sinara Mônica Vitalino; Silva, Lúcia Patrícia Bezerra Gomes; Lima, Luiza Rayanna Amorim; Botelho, Sandra Paula Sarinho; Lima, Maria do Carmo; Pitta, Ivan da Rocha; Beltrão, Eduardo Isidoro Carneiro; Carvalho Júnior, Luiz Bezerra
Abstract: Fluorescent compounds have been widely used for biomolecule labeling in cytochemistry and histochemistry analysis. Here, it is described the optical properties of dimethyl 2‐[(acridin‐9‐yl)methylidene]‐malonate (LPSF/IP‐81), an acridine derivative. This compound was conjugated to Concanavalin A (Con A) lectin and applied as sugar probe in lectin histochemistry. Evaluation of luminescent properties showed that LPSF/IP‐81 is photoluminescent with excitation at 360 nm and emission at 428 nm. Con A hemagglutinating activity and LPSF/IP81 photoluminescence were unaltered after conjugation. Circular dichroism of Con A‐LPSF/IP81 conjugate showed the maintenance of the Con A structure. Lectin histochemistry with Con A‐LPSF/IP81 conjugate demonstrated different pattern recognition studying normal, fibroadenoma, and invasive ductal carcinoma of human breast. These findings indicate that LPSF/IP‐81 can be proposed as an alternative probe for histochemical analysis. Abstract : Dimethyl 2‐[(acridin‐9‐yl)methylidene]‐malonate (LPSF/IP‐81) is an acridine derivative with photoluminescent properties; LPSF/IP‐81 was conjugated with Concanavalin A (Con A) lectin and applied as sugar probe in lectin histochemistry.